A Study on the College Students’ Employment Psychological Problems and Countermeasures in the Regular Prevention and Control of COVID-19–From the Perspective of Positive Psychology - et. al., Xia Zheng , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the normalization of epidemic prevention and control of COVID-19, the psychological problems of college students' employment have become more prominent. In this situation, college students' employment psychological problems are more complex than before, which to a large extent affects the students' employment psychology, employment objectives, but also affects the society's accurate selection of talents. This paper expounds the employment psychological problems of college students, from the perspective of positive psychology based on prevention, put forward coping strategies, to help college students to successfully complete the psychological adaptation and identity transformation from school to society, to achieve employment.